Understanding Generational Investment Patterns : A Behavioral and Socioeconomic Perspective - Moreno Pérez, Alfonso (My University, 2025)
This thesis investigates how investment strategies differ across generations and examines the underlying factors driving these variations. The study is based on Generational Theory and Behavioral Finance, investigating both structural effects, such as digital transformation and macroeconomic disruptions, as well as more personal and psychological components, such as confidence, risk tolerance, and behavioral bias. The analysis is based on 200 surveys collected across six different countries. The data was examined with non-parametric methods to ensure robust results. The findings reveal significant age disparities in risk tolerance (p = 0.0106), digital comfort (p = 0.0000), and the use of social media for investment decisions (p = 0.0000), emphasizing how technology and generational context has impacted on individuals’ approach to investing. By contrast, several of the parameters we expected to vary, such as the proportion of savings invested (p = 0.1025) or the impact of financial crises (p = 0.1710), did not reveal statistically significant differences across generations. The finding implies that whereas age influences some actions, others could be more universal. Among Gen Z respondents, a significant positive correlation (ρ = 0.57) between financial knowledge and confidence, suggests that self-directed learning and digital exposure are having an increasing impact on investor identity. As a whole, this investigation provides a fresh perspective on the investment strategies of each generation, which are not only different but also motivated by profoundly distinct factors. These findings could be useful for financial educators, legislators, and fintech companies looking to create more focused and inclusive financial solutions. By merging theoretical frameworks with real-world data, the study provides a new viewpoint on generational variations in financial behavior.
Grado en Administración y Dirección de Empresas Mención Internacional (E-4)
Keywords: 53 Ciencias económicas; 5302 Econometría; 530202 Modelos econométricos